COWRIE SHELLS IN OJO-ALAWORO: A NEXUS OF ART, CULTURE, TRADITION, HERITAGE, AND ECONOMIC DEVELOPMENT - AJAYI, Noah Oluwasanjo; ADEKOYA, Elizabeth Olanike (ShodhKosh: Journal of Visual and Performing Arts, 2022)
In the old days, most villages and towns of states and nations in Africa are founded with or through cowrie shells (owo eyo), thereby serving as evolutionary symbols and objects. There are several arts, cultures, traditions, heritages, and economic development (ACTHED) activities, cowrie shells (owo eyo) are being used in Nigeria and Africa generally, and Ojo-Alaworo town specifically, which is the target of this study. This ACTHED does not leave out socio-cultures, religion-magical and spiritual endowments. The aforementioned artistic activities are gradually facing out in our society through civilisation. Therefore, this study focuses on appraising and refreshing our memories of the significance and vital roles that cowrie shells (owo eyo) played and still play in the sojourn of the human race in Ojo-Alaworo town of Lagos State, Nigeria. In this regard, functionalism and symbolic interactionism theory of culture were used as a theoretical framework to analyze this study. As a qualitative research design, data were collected through semi-structured interviews (SSI) with five participants. They are indigenous elders (three males and two females) ages 70 to 85 years. The reason for this purposive sampling is that elders are wiser and more experienced in ACTHED, hence the Yoruba adage “iriri lagba”. The findings were discussed extensively which shows that cowrie shells (owo eyo) are inevitable in Ojo-Alaworo town despite civilisation in the town. To this end, a conclusion was made, and recommendations were suggested to revive the values of cowrie shells (owo eyo).